2008
DOI: 10.4049/jimmunol.181.6.4247
|View full text |Cite
|
Sign up to set email alerts
|

Acid Sphingomyelinase Amplifies Redox Signaling in Pseudomonas aeruginosa-Induced Macrophage Apoptosis

Abstract: Recent studies indicate that distinct membrane microdomains, also named lipid rafts, and ceramide play an important role in infectious biology. Ceramide forms larger ceramide-enriched membrane platforms that are required for diverse signal transduction. In this study, we demonstrate that ceramide-enriched membrane platforms are critically involved in redox signaling that regulates alveolar macrophage apoptosis upon infection with Pseudomonas aeruginosa. In freshly isolated alveolar macrophages, P. aeruginosa i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
109
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(116 citation statements)
references
References 38 publications
7
109
0
Order By: Relevance
“…We have recently demonstrated that ceramide plays a critical role in the development of cystic fibrosis and the high sensitivity of Cftr -deficient mice to P. aeruginosa infections [11, 20]. Employing biochemical, fluorescence microscopy and mass spectrometry techniques, we revealed an accumulation of ceramide in lungs, in particular in epithelial cells of large and small bronchi, in different Cftr -deficient mouse strains (Fig.…”
Section: Ceramide In Cystic Fibrosismentioning
confidence: 86%
See 3 more Smart Citations
“…We have recently demonstrated that ceramide plays a critical role in the development of cystic fibrosis and the high sensitivity of Cftr -deficient mice to P. aeruginosa infections [11, 20]. Employing biochemical, fluorescence microscopy and mass spectrometry techniques, we revealed an accumulation of ceramide in lungs, in particular in epithelial cells of large and small bronchi, in different Cftr -deficient mouse strains (Fig.…”
Section: Ceramide In Cystic Fibrosismentioning
confidence: 86%
“…Previous studies published by our group indicate that P. aeruginosa infection of epithelial cells and macrophages activates the acid sphingomyelinase and triggers a translocation of the enzyme onto the extracellular leaflet of the cell membrane [19, 20]. The activity of the acid sphingomyelinase triggers the formation of ceramide-enriched membrane platforms in the outer leaflet.…”
Section: P Aeruginosa Infections and Ceramidementioning
confidence: 96%
See 2 more Smart Citations
“…Ceramide may regulate neurogenesis via several pathways: Ceramide controls activity of Akt shown to be important for neuronal proliferation 21 . Ceramide has been also shown to regulate the formation of reactive oxygen species via activation of NADPH oxidases 22 , to mediate the effects of the cytokines interleukin (IL)-1β and tumor necrosis factor (TNF)-α [23][24][25] and to regulate stress-activated kinases 26 and calcium release 27 . Thus, ceramide may coordinate negative effects on hippocampal neurons by Akt inhibition and assembling of molecules involved in oxidative stress, proinflammatory receptors and stress-signaling.…”
Section: A-d)mentioning
confidence: 99%